Controlled trial of oral glucocorticoids in outpatients with acute COPD exacerbation who present to the emergency department: A randomized, double-blind, placebo-controlled pilot study. - Aaron, Shawn D (University of Ottawa (Canada), 1999)
Background. In North America, the prevalence of chronic obstructive pulmonary disease (COPD) amongst elderly patients is increasing, and COPD exacerbation is now a common cause for Emergency Department (ED) patient visits. Over 900 patient visits were logged at the Ottawa General and Civic Hospital's Emergency Departments in 1996 because of COPD exacerbation. Fifty-two percent of these ED patient visits for COPD resulted in a discharge home. Although exacerbations of COPD occur commonly, the optimal therapy of this condition remains unknown. It was felt that a state of clinical equipoise exists which justifies the need for a randomized, double-blind, placebo-controlled trial examining whether oral glucocorticoids should be used to treat patients with COPD exacerbation who are discharged home from the ED. This thesis will report on the results of the pilot study which was undertaken to establish the feasibility of a larger, definitive clinical trial. Objectives. The primary objective of the pilot study was to ensure that a larger clinical trial will be feasible. Secondary objectives of the pilot study were: to assess the rate of patient relapse in order to determine whether this clinical variable could serve as the primary outcome variable for the definitive study, to verify the sample size estimates for the larger trial, to evaluate patient referral rates and trial recruitment, and to verify the enrollment process and allow for pre-testing of the data collection and data analysis process. (Abstract shortened by UMI.)
Keywords: Health Sciences, Pharmacology.